Inter- and intramolecular aldol reactions promiscuously catalyzed by a proline-based tautomerase. Issue 13 (9th March 2017) - Rahimi, Mehran; Geertsema, Edzard M.; Miao, Yufeng; van der Meer, Jan-Ytzen; van den Bosch, Thea; de Haan, Pim; Zandvoort, Ellen; Poelarends, Gerrit J.
Abstract : The enzyme 4-oxalocrotonate tautomerase, which has a catalytic amino-terminal proline, was shown to promiscuously catalyze inter- and intramolecular aldol reactions. Abstract : The enzyme 4-oxalocrotonate tautomerase (4-OT), which in nature catalyzes a tautomerization step as part of a catabolic pathway for aromatic hydrocarbons, was found to promiscuously catalyze different types of aldol reactions. These include the self-condensation of propanal, the cross-coupling of propanal and benzaldehyde, the cross-coupling of propanal and pyruvate, and the intramolecular cyclizations of hexanedial and heptanedial. Mutation of the catalytic amino-terminal proline (P1A) greatly reduces 4-OT's aldolase activities, whereas mutation of another active site residue (F50A) strongly enhances 4-OT's aldolase activities, indicating that aldolization is an active site process. This catalytic promiscuity of 4-OT could be exploited as starting point to create tailor-made, artificial aldolases for challenging self- and cross-aldolizations.